2021
DOI: 10.1186/s12884-021-04195-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy and term delivery after treatment of unicornuate uterus with non-communicating rudimentary horn pregnancy with local methotrexate injection followed by laparoscopic resection: a case report and literature review

Abstract: Background Pregnancy in a rudimentary horn is an extremely rare type of ectopic pregnancy. A rudimentary uterine horn pregnancy is associated with a risk of spontaneous rupture and bleeding during surgery due to the increased uterine blood flow. Recent advances in imaging modalities have enabled laparoscopic surgery to be performed in cases without rupture in the early stages of pregnancy. However, there are few reports of successful pregnancies and deliveries after treatment of rudimentary hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(29 reference statements)
0
12
0
1
Order By: Relevance
“…Management of non-communicating rudimentary horn after diagnosis is the excision of the pregnant horn [ 8 ]. Laparoscopy is the standard treatment in hemodynamically stable patients; however, the threshold to convert to laparotomy should be low, given the typical hypervascularity of rudimentary horn pregnancies [ 3 , 5 , 10 ]. Recently, there have been case reports of combination medical and surgical management for rudimentary horn pregnancies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Management of non-communicating rudimentary horn after diagnosis is the excision of the pregnant horn [ 8 ]. Laparoscopy is the standard treatment in hemodynamically stable patients; however, the threshold to convert to laparotomy should be low, given the typical hypervascularity of rudimentary horn pregnancies [ 3 , 5 , 10 ]. Recently, there have been case reports of combination medical and surgical management for rudimentary horn pregnancies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy is the standard treatment in hemodynamically stable patients; however, the threshold to convert to laparotomy should be low, given the typical hypervascularity of rudimentary horn pregnancies [ 3 , 5 , 10 ]. Recently, there have been case reports of combination medical and surgical management for rudimentary horn pregnancies [ 5 ]. Ueda et al demonstrated methotrexate, intracardiac potassium chloride, or lidocaine injections as effective medical treatment options prior to surgery in order to decrease hypervascularity and overall complications [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations